Developing an African Offshoring Industry—The Case of Nigeria - Radwan, Ismail; Strychacz, Nicholas (World Bank, Washington, DC, 2012)
The purpose of this note is to raise awareness of Nigeria's potential as an African offshoring hub, and it is aimed primarily toward policy makers, potential private sector investors, and development partners. This note addresses the following questions: what can Nigeria do to take advantage of the benefits of global trade in services; how can the country brand itself as an offshoring destination for international investors; and what government policies are required to ensure that Nigeria plays a role in the growing Information communication technology (ICT) offshoring sector.